RELASI GENDER KAUM PEREMPUAN MISKIN DALAM BIDANG EKONOMI PADA TINGKAT PASAR KERJA SEKTOR FORMAL, INFORMAL DAN PENGEMBANGANNYA DALAM KEWIRASWASTAAN DI KOTA SEMARANG - Liliek Desmawati (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2007)
Form of unfair gender relationship oftentimes happened at impecunious woman who live in urban. Impecunious woman has been harmed by either through politics, social and also economic because their experience of marginalization, subordination and the stereotyping view. Problems of research are: (a) how gender relationship ofimpecunious woman in the field of economics and level of work market in informal and formal sector, (b) how to access their benefit and resource to develop better gender relationship, (c) do their gender relationship can be developed in private sector, and (d) how social culture influence the dynamics of gender relationship of impecunious woman in urban area? Research use qualitative approach, the data collecting technique use interview method ex• haustively which is structure, key informant is instructed to impecunious woman who lived in Semarang city. Data analysis use gender matrix analysis that loading activity, access and resource control, access benefit, activity impact to men and woman. Results show that gender relationship of impecunious woman at urban in the field of eco• nomics in formal sector ( public servant, private sector officer) have formed harmoniously, but in informal sector the woman tend to have no opportunity for reaching career path. The resource access to develop gender relationship among women are education (which is low in the most part), skill which supporting itswork, strong physical energy, high work motivation, persistent challenge either from family environment or from society, and credit asset to own house, except for car• parking women which not yet owned house alone. Access benefits of the gender relationship include prosperity offamily,improvement of woman prestige and status; involvement in decision-making processes and obtaining freedom for the actualization of their aspiration. Social control barrier to build fair gender relationship at formal sector consists of religion norm, family norm, and society cultural norm, but the fact is different in informal sector because there is almost no bureaucracy in this sector. Gender relationship can be developed in private sector (entrepreneurship) in the context of access benefit, but there are no evidence to woman who working as a public servant or a car• parking woman because they have no enthusiasm or willingness for being an entrepreneur. It is suggested to impecunious woman who wants to access job market to ready herself with training and education and also adequate skill so that they are not being marginalized and there also need and activity to increase awareness between men and women about domestic duties.